Students' readiness on practical learning in clothing engineering education: case on haute couture learning - Mahanani, Chytra; Supriyadi, Edy; Sukardi, Thomas; Listiani, Sri; Wahyuningsih, Urip (Journal of Education and Learning (EduLearn), 2025)
Haute couture-making techniques are critical competencies to be mastered by fashion engineering education (CEE) graduates. However, until now, many graduates have been unable to master these techniques optimally. Various studies and field phenomena confirm that they are unprepared for supporting knowledge (SK), socio-cultural, and psychological aspects. This phenomenon prompted us to measure practical learning readiness (PLR) in these three dimensions. In addition, we also examine the differences between dimensions and indicators and test the determination in constructing the PLR to determine the order of solving the problem. The survey was conducted on 386 CEE students with criteria who were currently studying haute couture (HC). The results of the descriptive analysis confirmed that psychological conditions (PC) and SK had a low level, while socio-cultural support had a high level. The results of the comparison test show that the three are generally similar, although there are notes in several indicators. Although all dimensions contribute significantly to constructing PLR, PC contribute the highest. This indicates that low PC are the first step to be addressed by CEE. Furthermore, several notes related to the decrease in knowledge-supporting practice are also the second effort that CEE must make to boost PLR in its students.